Sliding mode-based observer design for field-oriented control of induction machine drive for applications in hybrid electric vehicles - Hanif, Athar; Bhatti, Aamer Iqbal; Yassin, Abdul Rehman; Murtaza, Ghulam; Ahmed, Qadeer (Chinese Control Conference, 2014)
The feedback (direct) field-oriented (vector) control is the most commonly adopted instantaneous speed/torque control method for the hybrid electric vehicle's drive system. The feedback (direct) field-oriented (vector) control of induction machines primarily depends upon precise flux estimation. However, an accurate estimation of flux is hard due to the deviations in the machine's electrical parameters. Both the resistances (stator and rotor), which produces the imprecision in the flux estimation and in the generation of unit vectors, increase linearly with temperature, depending upon the temperature co-efficient of the resistance of the material. The unit vectors are used to guarantee correct alignment of stator direct-axis current with the flux vector and stator quadrature-axis current perpendicular to it. This provides the decoupled control as in separately-excited DC machines. Secondly, unit vectors are used for the purpose of control. Therefore, the imprecision of the estimated flux will degrade the performance of speed control. In this paper, a sliding mode based observer is presented subject to machine's electrical parameters variations. The mathematics and derivations of the proposed sliding mode observer is expressed. The performance and stability of the proposed observer is then worked out through the regulation problem of the 3-φ induction machine used for the implementation of field-oriented control for the application in hybrid electric vehicle. The results of the proposed observer shows the good performance in estimating the actual flux which is necessary for the accurate and exact performance of field-oriented control in hybrid electric vehicles. The proposed observer is also robust against the variations in rotor and stator resistance.